2019
DOI: 10.5039/agraria.v14i4a6642
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of the ‘Pera’ orange grafted onto nine rootstocks under the conditions of Rio Branco, Acre, Brazil

Abstract: Brazil is the world's largest sweet orange producer, but production in the state of Acre is small and does not meet the local demand, despite having climatic conditions that are adequate for its cultivation. The objective of this study was to evaluate the behavior of the 'Pera' orange using different rootstocks under the edaphoclimatic conditions of Rio Branco, Acre, Brazil. We grafted the scion of the 'Pera' orange onto nine citrus rootstocks: 'Cleopatra' mandarin, TSKFL x CTTR-013, LVK x LCR-038, TSKC x CTQT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Despite reports of abnormal graft union of 'Pera' with Cleopatra mandarin (Moraes et al 2011) and trifoliate hybrids (Carvalho et al 2018), no visual incompatibility symptoms were found in any of the evaluated scion/rootstocks combinations. Rodrigues et al (2019) also did not find symptoms in 'Pera' trees onto 'Indio' citrandarin and Schinor et al (2013) verified typical symptoms of incompatibility only in 'Pera' trees grafted onto two of the 42 evaluated hybrids 'Sunki' mandarin × trifoliate. According to Pompeu Junior and Blumer (2019), however, the incompatibility is not always readily expressed, which implies the need for a greater number of seasons of observations to reach definitive conclusions.…”
Section: Yapmentioning
confidence: 77%
“…Despite reports of abnormal graft union of 'Pera' with Cleopatra mandarin (Moraes et al 2011) and trifoliate hybrids (Carvalho et al 2018), no visual incompatibility symptoms were found in any of the evaluated scion/rootstocks combinations. Rodrigues et al (2019) also did not find symptoms in 'Pera' trees onto 'Indio' citrandarin and Schinor et al (2013) verified typical symptoms of incompatibility only in 'Pera' trees grafted onto two of the 42 evaluated hybrids 'Sunki' mandarin × trifoliate. According to Pompeu Junior and Blumer (2019), however, the incompatibility is not always readily expressed, which implies the need for a greater number of seasons of observations to reach definitive conclusions.…”
Section: Yapmentioning
confidence: 77%
“…On the other hand, the rootstock/scion ratio was lower (and closer to 1.00) on CL (1.17) and MP (1.28). Likewise, a good affinity in different citrus cultivars has also been found on MP [37] or CL [33,36].…”
Section: 'Lane Late' Navel Orange-rootstock Affinitymentioning
confidence: 80%
“…Many studies have reported the effect of citrus rootstocks on tree growth [11,[32][33][34]. In fact, substandard, semi-dwarfing, and dwarfing citrus rootstocks are known [35].…”
Section: 'Lane Late' Navel Orange Trees Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Field evaluations occurred on 14 and 15 May 2020 to measure the following plant biometric attributes (ground truth): height (hp), measuring the distance (perpendicular) from the highest leaf to the plant root collar, ground level; and crown diameter, in the same direction (Dl), perpendicular to the row (Dr), both obtained using a millimeter tape measure (positioned at half of the height of the plant under evaluation). The plant volume was then estimated according to the formula presented by Rodrigues et al (2019), Eq. ( 1):…”
Section: Collecting Biometric Attributesmentioning
confidence: 99%